A study on the evaluation of Indonesian local microbial phytase supplementation and its impact on broiler chicken performance, metabolic energy utilization, ileal histomorphology, and meat and bone mineralization - A. E. Suryani; A. S. Anggraeni; M. F. Karimy; L. Istiqomah; H. Herdian (Journal of the Indonesian Tropical Animal Agriculture, 2023)
The effect of local Indonesian microbial phytase, derived from L. plantarum A1-E extracted from the small intestine of Indonesian free-range chickens and C. tropicalis TKd-3 obtained from fermented Indonesian soybean tempe, on growth performance, metabolizable energy, ileal histomorphology, and meat and bone mineralization in broilers is the subject of evaluation in this study. A total of 140 day-old broiler chicks were divided into four treatments, five replicates, and seven chicks in each replicate. The research was carried out for 28 days. The experimental groups consisted of a basal diet without phytase (FA) serving as the negative control, a basal diet supplemented with 500 FTU/kg of L. plantarum A1-E phytase (FB), a basal diet supplemented with 500 FTU/kg of C. tropicalis TKd-3 phytase (FC), and a basal diet with commercial phytase as the positive control (FD). The results revealed that the broiler performance index increased by the FB and FC treatments (P<0.05), and the FC treatment exhibited a tendency to enhance metabolizable energy (P=0.06). The result of ileum histomorphology showed that the FB treatment increased villous height, the ratio of villous height to crypt depth, and villous surface area (P<0.05). The highest mineral content of phosphorus (P), magnesium (Mg), and iron (Fe) in broiler breast meat was obtained in the FB treatment (P<0.05). Furthermore, the highest mineral content of calcium (Ca), P, Mg, zinc (Zn), and Fe in thigh meat was found in the FC treatment (P<0.05). The mineralization of the tibia bone demonstrated that the FB treatment exerted a significant effect (P<0.05) on the P, Mg, and Fe mineral content. In conclusion, the performance index increased due to microbial phytase supplementation. Besides that, L. plantarum A1-E phytase improved the surface area of the villus, the absorption of ileum minerals, the mineral content of breast meat, and minerals deposition in the tibia.